Cardiac Depression Induced by Cocaine or Cocaethylene Is Alleviated by Lipid Emulsion More Effectively Than by Sulfobutylether‐β‐cyclodextrin. (23rd April 2015) - Fettiplace, Michael R.; Pichurko, Adrian; Ripper, Richard; Lin, Bocheng; Kowal, Katarzyna; Lis, Kinga; Schwartz, David; Feinstein, Douglas L.; Rubinstein, Israel; Weinberg, Guy; Heard, Kennon
Abstract Objectives Cocaine intoxication leads to over 500, 000 emergency department visits annually in the United States and ethanol cointoxication occurs in 34% of those cases. Cardiotoxicity is an ominous complication of cocaine and cocaethylene overdose for which no specific antidote exists. Because infusion of lipid emulsion (Intralipid) can treat lipophilic local anesthetic toxicity and cocaine is an amphipathic local anesthetic, the authors tested whether lipid emulsion could attenuate cocaine cardiotoxicity in vivo. The effects of lipid emulsion were compared with the metabolically inert sulfobutylether‐β‐cyclodextrin (SBE‐β‐CD; Captisol) in an isolated heart model of cocaine and cocaethylene toxicity to determine if capture alone could exert similar benefit as lipid emulsion, which exhibits multimodal effects. The authors then tested if cocaine and cocaethylene, like bupivacaine, inhibit lipid‐based metabolism in isolated cardiac mitochondria. Methods For whole animal experiments, Sprague‐Dawley rats were anesthetized, instrumented, and pretreated with lipid emulsion followed by a continuous infusion of cocaine to assess time of onset of cocaine toxicity. For ex vivo experiments, rat hearts were placed onto a nonrecirculating Langendorff system perfused with Krebs‐Henseleit solution. Heart rate, left ventricle maximum developed pressure (LVdevP), left ventricle diastolic pressure, maximum rate of contraction (+dP/dtmax), maximum rate of relaxation (–dP/dtmax), rate‐pressure product (RPP = heart rate × LVdevP), and line pressure were monitored continuously during the experiment. A dose response to cocaine (10, 30, 50, and 100 μmol/L) and cocaethylene (10, 30, and 50 μmol/L) was generated in the absence or presence of either 0.25% lipid emulsion or SBE‐β‐CD. Substrate‐specific rates of oxygen consumption were measured in interfibrillar cardiac mitochondria in the presence of cocaine, cocaethylene, ecgonine, and benzoylecgonine. Results Treatment with lipid emulsion delayed onset of hypotension (140 seconds vs. 279 seconds; p = 0.008) and asystole (369 seconds vs. 607 seconds; p = 0.02) in whole animals. Cocaine and cocaethylene induced dose‐dependent decreases in RPP, +dP/dtmax, and –dP/dtmaxabs (p < 0.0001) in Langendorff hearts; line pressure was increased by cocaine and cocaethylene infusion, but not altered by treatment. Lipid emulsion attenuated cocaine‐ and cocaethylene‐induced cardiac depression. SBE‐β‐CD alone evoked a mild cardiodepressant effect (p < 0.0001) but attenuated further cocaine‐ and cocaethylene‐induced decrements in cardiac contractility at high concentrations of drug (100 μmol/L; p < 0.001). Finally, both cocaine and cocaethylene, but not ecgonine and benzoylecgonine, inhibited lipid‐dependent mitochondrial respiration by blocking carnitine exchange (p < 0.05). Conclusions A commercially available lipid emulsion was able to delay progression of cocaine cardiac toxicity in vivo. Further, it improved acute cocaine‐ and cocaethylene‐induced cardiac toxicity in rat isolated heart while SBE‐β‐CD was effective only at the highest cocaine concentration. Further, both cocaine and cocaethylene inhibited lipid‐dependent mitochondrial respiration. Collectively, this suggests that scavenging‐independent effects of lipid emulsion may contribute to reversal of acute cocaine and cocaethylene cardiotoxicity, and the beneficial effects may involve mitochondrial lipid processing.